Nature and Extent of iPad Use among Freshmen Honors Students. (September 2013) - Maxwell, Patricia; Banerjee, Priya
On the heels of national studies reporting that college students believe tablet computers will "transform" learning, many colleges have begun to use mobile technology like the iPad and laptop as recruitment tools. The effectiveness of such incentives can be tested by determining whether enrollment increased as a result, and whether or not tablet computers found meaningful use. To this end, a study was conducted to examine the use of the iPad by freshmen honors students and the effect of the recruitment incentive on enrollment. The results revealed a significant difference in the anticipated and actual use of the iPad in social networking, multimedia, learning, lifestyle activities, and information management. Sixty-nine percent of the students reported that their decision to accept admission was influenced in large part by the iPad incentive.